Significance and causes of abnormal preoperative coagulation test results in children - Samková, A; Blatný, J; Fiamoli, V; Dulíček, P; Pařízková, E (Haemophilia, 2012)
To prevent bleeding related to adenoidectomy and tonsillectomy, coagulation screening tests were, until recently, performed routinely in the Czech Republic for all paediatric patients. The aim of this study was to evaluate benefit of preoperative coagulation screening tests in children. We retrospectively analysed laboratory and clinical data of children referred for abnormal preoperative coagulation test results (aPTT, PT) to the outpatient haematology clinic. A total of 274 paediatric patients were retrospectively evaluated due to abnormal preoperative coagulation tests results. In 140 of 274 patients (51.1%), coagulation tests were normal on repeated testing in a specialized haematology clinic. Ten patients had decreased factor XII. Five patients had a suspected bleeding disorder which was confirmed in two of them. One patient had low levels of von Willebrand factor, and one patient had mild factor VII deficiency. Both these patients had positive personal and/or family history of bleeding. Each case history was taken individually, without use of standardized questionnaires. Bleeding complications were not observed, and coagulation factor replacement was not needed perioperatively in our cohort. The majority of abnormal findings in aPTT and PT appeared only transiently. All the bleeding disorders found in our cohort of patients were mild in nature. Our findings provide supportive evidence for the current national Czech recommendation: laboratory coagulation screening should be performed only in patients with positive family and/or personal bleeding history.
Keywords: Blood Coagulation Factors; Tonsillectomy; adenektomie; Blood Coagulation Disorders; Female; Infant; předškolní dítě; dítě; tonzilektomie; ženské pohlaví; Predictive Value of Tests; prediktivní hodnota testů; Adenoidectomy; lidé; Postoperative Hemorrhage; plošný screening; kohortové studie; Cohort Studies; retrospektivní studie; pooperační krvácení; Male; koagulační faktory; Prothrombin Time; kojenec; Czech Republic; koagulopatie; Child, Preschool; protrombinový čas; Partial Thromboplastin Time; předoperační péče; Preoperative Care; Česká republika; parciální tromboplastinový čas; Child; Mass Screening; mužské pohlaví; Retrospective Studies; Humans